THE SUBSTANTIATION OF THE REGIONAL DEVELOPMENT STRATEGIES, PREMISE FOR THE ABSORPTION OF THE STRUCTURAL AND COHESION FUNDS IN ROMANIA - Aida, CATANĂ (Strategii Manageriale, 2014)
The process of the elaboration and the implementation of the regional development strategies is facing challenges coming both form the limits of the instruments which are used for the substantiation of the planning documents and the lack of the most efficient evaluation methods of the implementation measures impact. The regional development strategies developed within 2007 - 2013 programming period as parts of the Regional Development Plans were based on a series of statistical analyses of the available statistical data. The specific details of the of the administrative system, the capacity of the national and local public administration to lead the management and control system created for the absorption of the EU funds in Romania were missing from the regional development strategies. These are the problems identified both within the annual implementation reports and national strategic reports as the main causes of the low rate of absorption. As a conclusion, there are more different aspects such as capacity of the public management or the coherence of the legal system that should take into account in the process of the substantiation of the regional development strategies.